A security alarm system to detect intrusion using an Arduino, a GSM module, and a motion sensor - Muhammad Ahmad Baballe; Mukhtar Ibrahim Bello (Journal of Telecommunication Control and Intelligent System, 2021)
If the user power or activate the security system, the Arduino Uno will read the data when the motion sensor detects an intruder. The Arduino Uno microcontroller will activate the buzzer and sound an alarm, it will then display on the liquid crystal display (LCD) showing the intrusion. The GSM module gets the information from the Microcontroller it will send a short message service to the designated mobile number registered in the system with the help of the SIM card inserted in the GSM module that an intrusion has occurred. To communicate between the Mobile phone and GSM modem, AT command is applied to this research. This is because the GSM modem can only understand AT command declaration. From this, it can communicate with Mobile phones, computers, and Arduino microcontrollers.